The Effect of Planting Time Applications on Yield and Yield Properties in Some Soybean (Glycine max (L.) Merrill) Varieties - Tunçtürk, Murat; Mehmet BARIŞ; Tahsin SÖĞÜT (ISPEC Journal of Agricultural Sciences, 2020)
Abstract: This study was carried out to determine yield properties of some soybean cultivars under different sowing times in Diyarbakır ecological conditions in 2014. Field trial was designed in Completely Randomized Block Design with three replicates at experimental fields of Dicle University, Agricultural Faculty, Field Crops Department. Four different soybean cultivars (Atakişi, Arısoy, Blaze and Nazlıcan) and five different sowing times (1st of May, 20 st of May, 10 st of June, 25 st of June and 5 st of July) were the experimental factors. In this work, some phenological and agronomical parameters of soybean were investigated. As a result of the research, the highest yield of seed (2660.3 kg / ha) and oil (625.10 kg / ha) was obtained from the Arısoy soybean planted on July 5th. In addition, the highest plant height (99.67 cm) was obtained from the Nazlıcan variety planted on May 1st, and the highest pod number (46 units / plant) from the Atakişi variety planted on May 1st When the results obtained are evaluated, it is concluded that Arısoy soybean can be grown easily in the region. Keywords: Cultivar, Sowing date, Soybean, Yield, phenological properties